2014
DOI: 10.3109/08039488.2014.880942
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and specificity of the Brøset Violence Checklist as predictor of violence in forensic psychiatry

Abstract: The BVC showed satisfactory specificity and sensitivity as a predictor of the short-term risk of violence against staff and others by patients in a forensic setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 14 publications
0
21
0
1
Order By: Relevance
“…Several studies have investigated the psychometric properties of the BVC (Almvik, Woods, & Rasmussen, 2000;Bjorkdahl, Olsson, & Palmstierna, 2005;Hvidhjelm, Sestoft, Skovgaard, & Bue Bjorner, 2014;Yao et al, 2014) and the DASA (Barry-Walsh, Daffern, Duncan, & Ogloff, 2009;Chu et al, 2013;Dumais, Larue, Michaud, & Goulet, 2012;Griffith, Daffern, & Godber, 2013;Vojt, Marshall, & Thomson, 2010). Two cluster randomised controlled trials have demonstrated that the use of the BVC resulted in less aggression and a decreased use of restrictive practices (e.g., seclusion, mechanical restraint and the forced injection of medication) (Abderhalden et al, 2008;van de Sande et al, 2011).…”
Section: Risk Assessment Instrumentsmentioning
confidence: 99%
“…Several studies have investigated the psychometric properties of the BVC (Almvik, Woods, & Rasmussen, 2000;Bjorkdahl, Olsson, & Palmstierna, 2005;Hvidhjelm, Sestoft, Skovgaard, & Bue Bjorner, 2014;Yao et al, 2014) and the DASA (Barry-Walsh, Daffern, Duncan, & Ogloff, 2009;Chu et al, 2013;Dumais, Larue, Michaud, & Goulet, 2012;Griffith, Daffern, & Godber, 2013;Vojt, Marshall, & Thomson, 2010). Two cluster randomised controlled trials have demonstrated that the use of the BVC resulted in less aggression and a decreased use of restrictive practices (e.g., seclusion, mechanical restraint and the forced injection of medication) (Abderhalden et al, 2008;van de Sande et al, 2011).…”
Section: Risk Assessment Instrumentsmentioning
confidence: 99%
“…Fear of being exposed to dangerous situations and threats by patient violence is another source. Violence against healthcare providers has significant implications for both patients and staff . It has been reported that the majority of assaults against nurses occur in psychiatric departments .…”
Section: Discussionmentioning
confidence: 99%
“…Violence against healthcare providers has significant implications for both patients and staff. 34 It has been reported that the majority of assaults against nurses occur in psychiatric departments. 35 d'Ettorre and Pellicani 2 reported that between 7.5% and 33% of victims of violence later developed psychological symptoms, such as anxiety, depression, and avoidance behavior.…”
mentioning
confidence: 99%
“…In their initial study, Almvik et al (2000) reported that the tool had good psychometric properties with an AUC value of 0.82. Since then, the BVC has been evaluated in a number of studies in which the predictive validity of the tool has consistently been strong with an AUC of 0.85 (Yao et al, 2014), 0.92 (Hvidhjelm et al 2014), and 0.94 (Almvik et al 2007). The BVC has been reported to be quick and easy to administer by nurses (Almvik et al, 2007;Clarke et al 2010;Woods et al 2008;Yao et al 2014).…”
Section: Brøset Violence Checklist (Bvc)mentioning
confidence: 99%